Penerapan Partial Credit Model (PCM) dalam Mengevaluasi Tes Uraian: Application of Partial Credit Model (PCM) in Evaluating the Essay Tes - Ni Kadek Rini Purwati; I Wayan Sumandya (FPMIPA IKIP PGRI Bali, 2019)
The study, titled